"Adapting to New Climate Realities: Doing More, Better, and New" - Wiebe, Keith; Ringler, Claudia; Bryan, Elizabeth; Makhija, Simrin; Zhang, Wei; Arndt, Channing (2019)
Keith Wiebe, Claudia Ringler, Elizabeth Bryan, Simrin Makhija, Wei Zhang, and Channing Arndt POLICY SEMINAR Adapting to New Climate Realities: Doing More, Better, and New SEP 19, 2019 - 12:15 PM TO 01:45 PM EDT